2015
DOI: 10.1007/s41048-016-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas sp. LZ-Q continuously degrades phenanthrene under hypersaline and hyperalkaline condition in a membrane bioreactor system

Abstract: Graphical AbstractAbstractPhenanthrene is one of the most recalcitrant components of crude oil-contaminated wastewater. An efficient phenanthrene-degrading bacterium Pseudomonas sp. strain named LZ-Q was isolated from oil-contaminated soil near the sewage outlet of a petrochemical company. Pseudomonas sp. LZ-Q is able to degrade 1000 mg/L phenanthrene in Bushnell-Hass mineral salt medium. It also degrades other polycyclic aromatic hydrocarbons such as naphthalene, anthracene, pyrene, petrol, and diesel at broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…High performance liquid chromatography (HPLC; Agilent 1260 Infinity) was used to verify that NahG is involved in the conversion of salicylate to catechol 54 . The metabolites were separated with an Eclipse Plus C18 (4.6 mm × 250 mm).…”
Section: Methodsmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC; Agilent 1260 Infinity) was used to verify that NahG is involved in the conversion of salicylate to catechol 54 . The metabolites were separated with an Eclipse Plus C18 (4.6 mm × 250 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, after one month of cultivation, the fold increase in biomass was 2.5 times in terms of protein content (Figure 3). Several Pseudomonas strains have previously been described as capable of degrading PAHs such as PHE [44,45] or naphthalene [12]. Depending on the strain and the initial PHE concentrations, previous studies have reported biodegradation times ranging from two to fifteen days in liquid cultures [46] and from forty to sixty days in soil or reactor systems [44][45][46][47].…”
Section: Growth Of P Veronii Isolate Sm-20 In the Presence Of Phe As ...mentioning
confidence: 99%
“…Depending on the strain and the initial PHE concentrations, previous studies have reported biodegradation times ranging from two to fifteen days in liquid cultures [46] and from forty to sixty days in soil or reactor systems [44][45][46][47]. Additionally, concerning biomass growth, Pseudomonas strain LZ-Q and P. stutzeri ZP2 achieved a 10-fold increase in biomass production [44,48] in the presence of 1000 and 250 mg/L of PHE, respectively. On the other hand, strains of P. pseudoalcaligenes Several Pseudomonas strains have previously been described as capable of degrading PAHs such as PHE [44,45] or naphthalene [12].…”
Section: Growth Of P Veronii Isolate Sm-20 In the Presence Of Phe As ...mentioning
confidence: 99%
“…Pseudomonas is known for its metabolic versatility and capacity to produce abundant secondary metabolites [6,12]. They can utilize various chemical compounds as sources of carbon, nitrogen, or phosphorus, making them interesting microorganisms for processes such as bioremediation and biotransformation [2,13]. For example, Pseudomonas mediteranea S58 can produce siderophores, amylase, and protease, solubilize organic phosphorus, and show strong antagonism against a variety of plant pathogenic fungi and bacteria [14].…”
Section: Introductionmentioning
confidence: 99%